Characterization of the mechanism of Scutellaria baicalensis on reversing radio-resistance in colorectal cancer - Jinmei Huang; Ming Zhou; Huan Zhang; Yeying Fang; Gang Chen; Jiaying Wen; LiMin Liu (Translational Oncology, 2022)
Scutellaria baicalensis (SB) has been shown to improve the therapeutic effects of colorectal cancer (CRC) and perform well for reversing radio-resistance in different cancers. However, its potential function and mechanism related to radio-resistance in CRC has not been explored. A radio-resistant human CRC cell line (HCT116R) was applied. A network pharmacological analysis was performed to reveal the potential mechanism of SB for reversing radio-resistance in CRC, and computational pathological analysis was applied to indicate the clinicopathological significance of the key targets. Then, our hypothesis was further verified by molecular docking. The network pharmacology analysis showed that wogonin is the key compound of SB for reversing the radio-resistance of CRC. A Kyoto Encyclopedia of Genes and Genomes analysis showed that the genes for SB that reverse radio-resistance in CRC are mainly involved in steroid hormone biosynthesis. An enrichment analysis pointed out that Sulfotransferase family 2B member 1 (SULT2B1) is a potentially vital gene. SULT2B1 was demonstrated as being highly expressed in CRC and upregulated in radio-resistant rectal tissues or cell lines. A CCK-8 and clone formation test showed that the viability and clone formation ability of HCT116R were significantly decreased by wogonin combined with radiotherapy, compared to radiotherapy alone. By contrast, flow cytometry revealed that the apoptosis of HCT116R was significantly increased when wogonin treatment combined with radiotherapy, compared with radiotherapy alone. Molecular docking verification indicated that SULT2B1 and wogonin have a good binding ability. Taken together, SULT2B1 may be the potential drug target in treating radio-resistant CRC. Wogonin may be the core compound of SB for reversing radio-resistance in CRC by targeting SULT2B1.